Physico-chemical studies and evaluation of diuretic activity of Cucurbita maxima - Venkattapuram Sampath Saravanan; Sellimuthu Manokaran (Bangladesh Pharmacological Society, 2012)
In this study physico-chemical nature and diuretic activity was evaluated to establish the purity and diuretic activity by comparing with the standard acetazolamide. Pulp of Cucurbita maxima is a common cost effective Indian dish, rich in nutrients. Physico-chemical parameters like ash values, extractive values and loss on drying were performed to find the purity. The hydro-alcoholic extract was prepared by extracting the powder in soxhlet apparatus for 36 hrs. The laboratory qualitative analysis was done and constituents like carbohydrates, proteins, lipids, flavonoids, alkaloids and vitamin C were found. The two doses of extract (150 and 300 mg/kg) were given to the rats. Group I served as control, Group II served as standard and Group III and IV served as test. Electrolytes and urine volume was measured after 5 hrs of treatment and the same was compared with the control and the standard drug acetazolamide. Physico-chemical parameters were in the limit and the extract shows significant (p<0.01) diuretic activity at the dose of 300 mg/kg when compared with control.